Control of Home Blood Pressure with an Amlodipine- or Losartan-Based Regimen and Progression of Carotid Artery Intima-media Thickness in Hypertensive Patients: The HOSP Substudy. (July 2013) - Ohta, Yuko; Kawano, Yuhei; Iwashima, Yoshio; Hayashi, Shinichiro; Yoshihara, Fumiki; Matayoshi, Tetsutaro; Takiuchi, Shin; Kamide, Kei; Nakamura, Satoko; Horio, Takeshi
<x xml:space="preserve">Abstract</x> Carotid artery intima-media thickness (IMT) has emerged as a predictor of cardiovascular events. Home blood pressure (BP) is more closely associated with cardiovascular prognosis than clinic BP. The aim of this study was to compare the progression of carotid IMT with respect to strict and mild control of morning home systolic BP (SBP) and amlodipine- and losartan-based antihypertensive therapy in hypertensive patients. Subjects included 80 hypertensive outpatients who participated in the Hypertension Control Based on Home Systolic Pressure (HOSP) pilot study. After a 1-month drug-free period, the patients were randomly assigned to either the strict control group (target SBP <130 mm Hg) or the mild control group (130–139 mm Hg) and to either the amlodipine group or the losartan group. Additional antihypertensive drugs were added if target BP was not achieved with monotherapy. Morning SBP achieved target levels during 5 years in the strict control group and in the mild control group, while it was comparable between amlodipine and losartan groups. In all patients, mean and maximum carotid IMT increased significantly. Changes in carotid IMT did not differ between strict and mild control groups. Changes in mean carotid IMT in amlodipine group were smaller than those in losartan group at year 1, but were not different between the two groups at year 5. In conclusion, carotid IMT increased over time in hypertensive patients in spite of the strict control of home BP. Amlodipine may slow the progression of IMT more than losartan, although a difference was not obvious after 5 years.